Асинхронні генератори автономних зварювальних комплексів. Розвиток теорії та дослідження - Мазуренко, Л.І.; Джура, О.В. (Технічна електродинаміка, 2011)
The results of theoretical and experimental investigations made during 2007􀃭2010 years in the department of electromechanical systems of Institute of Electrodynamics of National Academy of Sciences of Ukraine, on the research work ”Asingen-2“ are set forth. The obtained results are made for theory development and improvement of welding complexes that are based on brushless induction generators with exciters carried out on power electronics and capacitors, units of forming the output characteristics and single-phase auxiliary generators.